The Role of The Social Studies Teacher to Form Social Skills of Students in The Industry Era 4.0 - Karamina, Sharfina; Arsal, Thriwaty; Sanjoto, Tjaturahono Budi (JESS (Journal of Educational Social Studies), 2019)
Disrupting behavioral issues can be social development of young people in the interaction that effective with others and the environment. The objectives of this study to analyze students social skills, explain and analyze the role of social studies teachers to form students' social skills.Focus research includes the characteristics of social skill and role of teachers in their experiences social studies.The research approach used is descriptive qualitative research with a design case study.The data collection was carried out by interviewing informants consisting of students, social studies teachers, guidance counseling teachers and school principals.Observation performed on learning process social studies in the classroom.The research results show that the characteristics of social skill on students interpersonal that in behavior, behavior that deals with yourself, behavior that deals with academic success, the reception of their peers, and how to communicate.Social studies learning that used lecture method to be problem based learning method requires students to learn independently. The research conclusion is the role of social studies teachers in learning in the classroom has an important role to form the social skills of students, especially with the cooperation with students. The new finding the teacher social studies in learning indicated with awareness teachers in evaluating myself and innovation in provide learning active and pleasing in the classroom.